Endoscopic ultrasound-guided rendezvous for biliary access after failed cannulation - Iwashita, T.; Lee, J. G.; Shinoura, S.; Nakai, Y.; Park, D. H.; Muthusamy, V. R.; Chang, K. J. (Endoscopy, 2012)
Introduction: Selective cannulation fails in approximately 3 % of endoscopic retrograde cholangiography (ERC) procedures. An endoscopic ultrasound-guided rendezvous technique (EUS – RV) may salvage failed cannulation. The aims of the current study were to determine the safety and efficacy of EUS – RV. Methods: A total of 40 patients underwent salvage EUS – RV. EUS – RV was attempted immediately after failed biliary cannulation. A dilated intra- or extra-hepatic biliary duct (IHBD or EHBD) was punctured from the stomach or the small intestine under EUS guidance followed by cholangiography and antegrade manipulation of the guide wire into the small intestine. Finally, the echoendoscope was exchanged for an appropriate endoscope and biliary cannulation was achieved over or adjacent to the guide wire.Result: EUS–RV appears safe and effective and may be considered as a primary salvage technique after failed cannulation. Antegrade manipulation of the guide wire into the small intestine was achieved in 29 of 40 patients (73 %; EHBD 25 /31 and IHBD 4/9). The reasons for failure were inability to advance the guide wire through an obstruction or a native ampulla. Re-attempt at ERC immediately after failed EUS – RV was made in seven of the 11 patients, and was successful in four. The remaining seven patients underwent percutaneous drainage within 3 days. Complications occurred in five patients (13 %), including pancreatitis, abdominal pain, pneumoperitoneum, and sepsis/death, which was unlikely to be related to the procedure.Conclusion: EUS – RV is safe and effective and should be considered as a primary salvage technique after failed cannulation. Immediate re-attempt at ERC after failed EUS – RV is warranted, as EUS-guided cholangiogram can facilitate biliary cannulation in some cases. Finally, prompt alternative biliary drainage should be available.